Gastrointestinal Parasitism and Co-infection Patterns in Quarantined Olive Baboons at the Kenya Institute of Primate Research – Retrospective Analysis (2012–2013) (Sahel Journal of Life Sciences FUDMA, 2025)
Gastrointestinal (GI) parasitism remains a major health and welfare concern among captive and quarantined non-human primates (NHPs). This retrospective study assessed the prevalence and patterns of GI parasites among quarantined olive baboons (Papio anubis) received between 2012 and 2013 at the Kenya Institute of Primate Research (KIPRE), Nairobi, Kenya. Faecal examination records from both cohorts were reviewed to determine infection prevalence, parasite diversity, co-infection patterns, and associations with host factors (sex, age, and body weight). Results revealed an overall infection prevalence of 98% in the 2012 cohort and 99% in 2013, with protozoan infections predominating (96.0% and 97.2%, respectively). The most frequently detected protozoa were Entamoeba spp. and Balantidium coli, while strongyles were the dominant helminths. Co-infections were common, affecting over 97% of infected baboons, with triple and quadruple infections accounting for 40% and 25–30% of cases, respectively. No significant associations were found between infection status and sex, age, or weight, suggesting uniform exposure across host groups. The 2013 cohort exhibited a lower helminth prevalence compared to 2012, possibly indicating improvements in quarantine management practices. These findings highlight the persistent challenge of GI parasitism, particularly protozoan infections, in quarantined baboons and underscore the need for targeted parasite control strategies, improved environmental hygiene, and comprehensive health monitoring to enhance animal welfare and reduce zoonotic risks.